2016
DOI: 10.5664/jcsm.5582
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Characteristics of REM Sleep without Atonia (RSWA) in Patients Taking Antidepressants

Abstract: Study Objectives: The association of REM sleep without atonia (RSWA) as well as REM sleep behavior disorder (RBD) with the intake of selective serotonin reuptake inhibitors (SSRI) and selective norepinephrine reuptake inhibitors (SNRI) is well established. Our study objective was to determine the prevalence of RSWA and RBD among a group of sleep center patients taking SSRI and SNRI. Methods: A retrospective chart review was done at our tertiary sleep center, and 10,746 consecutive records from October 1, 2007,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 26 publications
0
36
0
2
Order By: Relevance
“…Another limitation is the preponderance of subjects suffering from comorbid psychiatric conditions, which may also reduce generalizability, albeit a number of recent works suggest that a substantial proportion of treatment-seeking OSA subjects report a history of mental health conditions or use of psychotropic medications. [52][53][54][55][56][57] Last, among the subgroups who did not pursue PAP (no titration or prescription), anecdotal insights suggest that 19 patients specifically refused this treatment very early in the process, which may relate to the work of Brostrom et al 58 on PAP rejection by subjects with Type D personality (eTable 1).…”
Section: Limitationsmentioning
confidence: 99%
“…Another limitation is the preponderance of subjects suffering from comorbid psychiatric conditions, which may also reduce generalizability, albeit a number of recent works suggest that a substantial proportion of treatment-seeking OSA subjects report a history of mental health conditions or use of psychotropic medications. [52][53][54][55][56][57] Last, among the subgroups who did not pursue PAP (no titration or prescription), anecdotal insights suggest that 19 patients specifically refused this treatment very early in the process, which may relate to the work of Brostrom et al 58 on PAP rejection by subjects with Type D personality (eTable 1).…”
Section: Limitationsmentioning
confidence: 99%
“…EC's clinical picture of depressed mood, poor sleep and anorexia made mirtazapine an attractive treatment option. There was concern, however, his prior reaction to SSRI medications and the known association of SSRIs and SNRIs with exacerbation of RBD [5] that he would experience worsening in his disordered sleep behaviors. A literature search revealed less risk of exacerbation of RBD with mirtazapine as compared to SSRI and SNRI medications, though case studies have been reported [6].…”
Section: Discussionmentioning
confidence: 99%
“…Mirtazapin sowie SSRI und SNRI können die Symptome einer REM-Schlaf-Verhaltensstö-rung verursachen. Diese äußert sich in einer krankhaften Aufhebung der Muskelentspannung im Schlaf und führt zu einem Ausagieren von Trauminhalten (16). Normalerweise ist die Muskulatur im Traumschlaf besonders stark gelähmt, um genau vor diesem Phänomen zu schützen.…”
Section: Parasomnienunclassified